KOMUNITAS HERPETOFAUNA DI TAMAN NASIONAL GUNUNG CIREMAI, JAWA BARAT - Riyanto, Awal (Perhimpunan Biologi Indonesia, 2008)
ABSTRACTHerpetofaunal Community Structure of Ciremai Mountain National Park, WestJava. Distribution and broad habitat associations of the herpetofauna on four limitedsites of Ciremai mountain, west Java, Indonesia were studied. The field surveys wereconducted on Apuy-Arban site from 7 until 21 April 2006 and from 6 until 10 March2007, Linggarjati site from 10 until 15 February 2007 and from 19 May until 2 June2007, Seda forest from 18 until 24 February 2007 and Palutungan site from 26 Februaryuntil 4 March 2007. A variety of methods were employed to sample the herpetofauna. Atotal of 43 amphibians and reptiles taxa were recorded, comprising 16 frogs, 18 lizardsand 9 snakes. Two of them were endemic to Java, they are Huia masonii and Microhylaachatina. Unidentified and possibly undescribed species of unusual specimen referred tothe genus Elapoidis. From this study, three habitat were clustered and divided into twomain habitat zones for herpetofauna.Key words: amphibians, reptiles, gunung Ciremai.